Implementation of the Brocleanx Application for Optimizing Android Based Shoe Cleaning Management - Ervin Khoirus Syifa' Uddin; Sulistyo Dwi Sancoko (Komunitas Dosen Indonesia, 2025)
This research addresses operational inefficiencies within local service SMEs by detailing the development of a mobile booking application for the Brocleanx case study. The pre existing manual booking system resulted in significant inefficiencies and a lack of real time tracking. The innovation of this research lies in its integrated approach, which combines Location Based Service (LBS) for booking logistics accuracy with end to end service transparency through real time order status tracking. This study adopts a structured waterfall development methodology, encompassing requirements analysis, system design, implementation, and functional testing using the Black Box method. The resulting application enables customers to book pick up and delivery services, specify their location accurately via LBS for efficient logistics, and track order status in real time. Supporting features include transaction history and automated notifications. Developed using Flutter for the UI and Supabase as a Backend as a Service (BaaS), the application was validated through functional testing. This testing confirmed the successful operation of core functionalities, achieving an 85.7% pass rate. Findings indicate that the application successfully transformed manual business processes into a centralized digital system, significantly improving operational efficiency by addressing the previous 15% order data error rate and 10 minute administrative work time order, while simultaneously enhancing customer convenience through transparent monitoring. This study concludes that the LBS-integrated mobile booking application is an effective solution for improving service quality at Brocleanx. Furthermore, this implementation serves as a practical model for other local service SMEs seeking to digitize their operations by enhancing logistics efficiency and customer transparency.